2014
DOI: 10.4067/s0718-34292014000400006
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of the drying kinetics of the leaves of lemon grass (Cymbopogon citratus Stapf) and its effects on quality

Abstract: The aim of this study was evaluate the drying of the lemon grass plant (Cymbopogon citratus Stapf) at different air temperatures (40 °C, 50 °C, 60 °C and 70 °C) to adjust the experimental data obtained with different mathematical models and assess the quality of the plant after drying. A completely randomized design (CRD) was used with three drying replications for each speed and temperature of the drying air. The essential oil content extracted from the dried plant at 0.8 m s -1 and 1.3 m s -1 with manual co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…The loss of quality in oven-dried leaves, especially at higher temperatures, can be attributed to browning reactions at higher temperatures, a decrease in chlorophyll content and essential oils (Coradi et al, 2014;Chen & Patel, 2008;Kassem et al, 2006;Sanmeema et al, 2012). With respect to the effect of air velocity on quality of dried leaves, Coradi et al (2014) found that increasing the air velocity from 0.8 to 1.3 m/s did not negatively affect the essential oil content of lemongrass leaves when compared with fresh leaves; however, further increasing the velocity to 1.8 m/s resulted in a statistically significant reduction in oil content. They noted the works of Buggle et al (1999) who dried lemongrass leaves at 30-90°C and found that the highest oil content of 1.43% was found in leaves dried at 50°C.…”
Section: Ta B L E 3 Color Attributes Of Fresh and Dried Lemongrass Lementioning
confidence: 99%
See 4 more Smart Citations
“…The loss of quality in oven-dried leaves, especially at higher temperatures, can be attributed to browning reactions at higher temperatures, a decrease in chlorophyll content and essential oils (Coradi et al, 2014;Chen & Patel, 2008;Kassem et al, 2006;Sanmeema et al, 2012). With respect to the effect of air velocity on quality of dried leaves, Coradi et al (2014) found that increasing the air velocity from 0.8 to 1.3 m/s did not negatively affect the essential oil content of lemongrass leaves when compared with fresh leaves; however, further increasing the velocity to 1.8 m/s resulted in a statistically significant reduction in oil content. They noted the works of Buggle et al (1999) who dried lemongrass leaves at 30-90°C and found that the highest oil content of 1.43% was found in leaves dried at 50°C.…”
Section: Ta B L E 3 Color Attributes Of Fresh and Dried Lemongrass Lementioning
confidence: 99%
“…Oven (cabinet) drying still remains an attractive option for bulk drying of fragrant leaves such as coriander, olive mint, basil, thyme, bay leaves, and olive leaves (Ahmed, Shivhare, & Singh, 2001;Erbay & Icier, 2010;Cakmak, Kumcuoglu, & Tavman, 2013;Rodríguez, Clemente, Sanjuán, & Bon, 2014;Doymaz, 2014). A review of the work performed on lemongrass reveals studies which focus on different aspects of the drying process, including quality and essential oil content (Lonkar, Chavan, Pawar, Bansode, & Amarowicz, 2013;Martinazzo et al, 2009), drying efficiency (Kassem, El-Batawi, & Sidky, 2006), effect of pretreatments (Lonkar et al, 2013), drying curves (Coradi, Melo, & Rocha, 2014;Fudholi et al, 2012;Ibrahim, Sopian, & Daud, 2009;Rahman, Tasirin, Razak, Mokhtar, & Muslim, 2013), and mathematical modeling of drying data (Coradi et al, 2014;Ibrahim et al, 2009;Kemat, Rahman, & Wahit, 2008;Waewsak, Chindaruksa, & Punlek, 2006). However, with respect to the drying method employed, there are limited studies on lemongrass which include conventional cabinet drying (Kassem et al, 2006;Lonkar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations